2021
DOI: 10.1101/2021.03.01.21252652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early effectiveness of COVID-19 vaccination with BNT162b2 mRNA vaccine and ChAdOx1 adenovirus vector vaccine on symptomatic disease, hospitalisations and mortality in older adults in England

Abstract: Objectives To estimate the real-world effectiveness of the Pfizer/BioNTech BNT162b2 vaccine and Astrazeneca ChAdOx1 vaccine against Confirmed COVID-19, hospitalisations and deaths. To estimate effectiveness on the UK variant of concern. Design Test negative case control design Setting Community COVID-19 PCR testing in England Participants All adults in England aged 70 years and older (over 7.5 million). All COVID-19 testing in the community among eligible individuals who reported symptoms between 8th Decemb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
185
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(208 citation statements)
references
References 15 publications
17
185
3
3
Order By: Relevance
“…ChAdOx1 nCoV-19 has been deployed in the UK national vaccination programme since Jan 4, 2021, during which time B.1.1.7 has been the dominant circulating lineage. 13 Early national vaccine effectiveness data has shown that a single dose of ChAdOx1 nCoV-19 confers protection from both symptomatic disease and COVID-19-related hospitalisation, 47 consistent with the findings presented here. No participants in this study had evidence of the novel E484K (Glu484Lys) spike mutation first described in the B1.351 lineage identified in South Africa.…”
Section: Discussionsupporting
confidence: 88%
“…ChAdOx1 nCoV-19 has been deployed in the UK national vaccination programme since Jan 4, 2021, during which time B.1.1.7 has been the dominant circulating lineage. 13 Early national vaccine effectiveness data has shown that a single dose of ChAdOx1 nCoV-19 confers protection from both symptomatic disease and COVID-19-related hospitalisation, 47 consistent with the findings presented here. No participants in this study had evidence of the novel E484K (Glu484Lys) spike mutation first described in the B1.351 lineage identified in South Africa.…”
Section: Discussionsupporting
confidence: 88%
“…This would imply that the relative efficacy of the first dose ( VE R ) is in the region of 93% for the Pfizer vaccine and the Oxford/AstraZeneca vaccine. More recent data from the UK on mortality in those over 80 years old suggests that the first dose reduces deaths by around 80%, which acts as a lower bound for the relative efficacy of the first dose against mortality [7].…”
Section: Methodsmentioning
confidence: 99%
“…The vaccines already developed represent a major technological achievement and have been shown to generate significant immune responses, as well as offering considerable protection against disease [15]. Field data from Israel and the UK suggests that protection against severe disease (hospitalisation or death) may be even greater [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…The vaccination programme began to be rolled out in earnest from late December 2020 and early January 2021 in England, and to date over 17 6 million adults in England have received their first dose of vaccine [4]. Results from population studies indicate that one dose of either BNT162b2 mRNA or ChAdOx1 COVID-19 vaccines confers not only a reduction in risk of severe infection and hospitalisation but is also protective against symptomatic infection [11].…”
Section: Discussionmentioning
confidence: 99%